Conformance Level of Histopathological Examination in BiopsyPre Colonoscopy Compared to Histopathological Examinationin Surgery with Tumors in the Colon at The Endoscopy andGastrointestinal Centre of RSCM - Fuadi, Ifransyah; Makmun, Dadang; Krisnuhoni, Ening (UI Scholars Hub, 2017)
Introduction. Level of agreement comparison between biopsy per colonoscopy examination is used to measure of the quality of a colonoscopy examination and needed to be identified. This study aims to identify level of agreement comparison between histopathologic examination of biopsy per colonoscopy and histopathologic examination per surgical. Methods. A cross sectional study was conducted by using medical records from patients with colon tumor who had undergone histopathologic examination with biopsy per colonoscopy and then confirmed by surgical procedure in PESC RSPUN dr. Cipto Mangunkusumo between 1st January, 2006 31st December, 2015. Level of agreement calculated using comparative agreement category test in order to obtain the value of kappa. Results. A total of 48 subjects were included in this study. Analysis result showed that level of real agreement, level of agreement by chance, and level of agreement not by chance was 79%, 77%, and 23%, respectively. The kappa value was 0,134. Conclusion. The level of agreement comparison between histopathologic examination of biopsy per colonoscopy compared with histopathologic examination per surgical at PESC RSCM between 2006-2015 period was not good.